EFEKTIFITAS PENGGUNAAN CENDAWAN MIKORIZA TERHADAP PERTUMBUHAN BIBIT KAKAO SAMBUNG PUCUK (Theobroma cacao L.) DI KABUPATEN SIKKA - Yovita Yasintha Bolly; Yuyun Wahyuni (AGRICA, 2021)
The use of mycorrhizal biofertilizers in shoot grafting cacao (Theobroma cacao L.) nurseries is one of the efforts made to increase cocoa growth in Sikka Regency. This study aims to determine the effect of the dose of mycorrhizal biological fertilizer on the growth of cocoa seedlings. The study used a randomized block design (RAK) with fertilizer doses of 0 g/polybag (control), 10 g/polybag, 20 g/polybag, 30 g/polybag, 40 g/polybag 50 g/polybag. The results showed that the treatment the addition of mycorrhizae on shoot grafting cocoa seedlings had no effect on all growth variables observed at 30 days after mycorrhizal application and significantly affected all growth variables for cacao seedlings aged 60 days after mycorrhizal application. Giving mycorrhizae to shoot grafting cocoa seedlings at a dose of 50 g/polybag (M5) gave the highest yield for all growth variables of cocoa seedlings aged 60 days after mycorrhizal application, namely plant height 48.50 cm, stem diameter 1.10 cm, and number of leaves 8 ,25 strands.